MATHEMATICAL MODEL OF PHOTOPLETYSMIC SIGNAL AS THE BASE FOR INFORMATIONAL PARAMETERS IDENTIFICATION - Martchenko, Borys; Mlynko, Bogdana; Fryz, Mykhaylo (International Journal of Computing, 2014)
Taking into account the biophysical genesis of researched signal and its rhythmic nature the new mathematical model of photopletysmic signal as a linear periodical random process is developed; characteristic functions analysis of signal, experimental informational parameters estimating are possible with this model.